Anticedent of Capital Structure for MNC - Beby Kendida Hasibuan; Khaira Amalia Fachrudin; Maria Monica Sihombing (Enrichment : Journal of Management, 2022)
Multinational companies are companies that carry out business activities internationally in many countries and have subsidiaries in more than one country. This study aims to analyze whether there is an influence of the firm size (size), asset growth (GP), Return on Asset (ROA), Current Ratio (CR), Fix Assets Ratio (FAR), Sales Growth (TP) on Capital Structure (DER). This study uses a quantitative method with the 2013-2022 observation year in 23 multinational companies. The analysis technique used is multiple regression analysis. From the results of the study showed that 1. ROA and SIZE have a negative and significant effect on DER, 2. FAR and CR have a positive and significant effect on ROA, 3. whereas TP and GP have a positive and not significant effect on DER.